Penerapan Take Away Sebagai Konsep Dan Strategi Penjualan Pada Outlet Makanan Cepat Saji: Case Study Hakui Kopi Tulungagung - Dhiya’u Shidiqy, (JOURNAL KOPERASI DAN MANAJEMEN, 2022)
Purpose – This study was conducted with the aim of describing the concept of selling with a takeaway at Hakui Kopi Tulungagung Station and is the first research that focuses on the concept of takeaway as a sales strategy. Design/methodology/approach – The approach in this study uses a descriptive qualitative approach with analytical techniques using an interactive analysis model. Findings – The results showed that the number of takeaway purchase orders at Hakui Kopi Station was more dominant than purchase orders with online and dine-in applications. At the same time, product units sold were dominated by online purchases. The factors of distance and access to the shop are also quite dominant motives compared to other motives, namely psychological, lifestyle, socioeconomic, and advertising effects. Research limitations/implications – There is also the practicality of ordering and the suitability of consuming are the dominant factors in the background and become the motives of consumers in making takeaway purchases. Originality/value – The practicality of ordering and serving are the primary reasons and motivations for purchasing, according to the findings of observations on customer interest and motivation in selecting to purchase takeout at Hakui Kopi Station. Distance and accessibility are the second most important reasons and motives for purchasers to purchase takeout.